Mechanical characterisation and replication quality analysis of micro-injected parts made of carbon nanotube/polyoxymethylene nanocomposites. (March 2018) - Pagano, Claudia; Surace, Rossella; Bellantone, Vincenzo; Baldi, Francesco; Fassi, Irene
The increasing demand for small and cheap parts is boosting the development of reliable micro-system technologies. Fabrication process capabilities should expand to encompass a wider range of materials and geometric forms, which can satisfy the specific requirements of new emerging micro-products, and ensure the compatibility of new materials and processing technologies. Polymeric composites are very promising materials, since they offer new combinations of properties not available in traditional homogeneous materials. Because of their advantageous light weight, high strength, fatigue life, and corrosion resistance, they are forecast to replace conventional materials in several applications. Among the plastic process technologies, injection moulding is one of the key technologies for manufacturing miniaturised components due to its mass production capability and relatively low production cost. Micro-injection moulding allows to transfer micron and even submicron precision features to small products. Since final product properties strongly depend on materials and production processes and parameters, the process conditions of compounding as well as of product manufacturing have to be carefully studied and controlled. This is particularly important for the manufacturing of micro-products, since, at the micro-scale, some phenomena negligible at the macro-scale (as hesitation effect or capillarity forces for examples) can become important. However, only few studies concern the micro-injection of nanocomposites. Therefore, in this paper the micro-injection of two composites made of polyoxymethylene and carbon nanotubes has been studied. First, the electrical properties of the compounds have been measured; the fillers are dispersed in the matrix and form a network that dramatically increases the conductivity of the composites in comparison with the pristine resin. Then the compounds have been injected using a micro-injection machine and the components have been analysed. The mechanical analysis, based on tensile tests and dynamic-mechanical experiments on miniaturised dog-bone specimens, shows a slight reinforcing effect of the filler; however, the ductility is considerably reduced. This is likely due to a scarce adhesion of the carbon nanotubes and the polymer and the presence of some agglomerates. Moreover, as expected, the mould temperature affects the mechanical properties of the specimens, probably due to its effect on the internal structure of the solidified materials. The dimensional analyses carried out on micro-rib specimens show that replication capability is increased by the presence of the filler and using high values of the process parameters. Finally, microscopic analyses have been done in order to verify the dispersion and orientation of the fillers in the compounds. These effects have been observed only when high shear rates are involved.